Functional outcomes after transoral robotic surgery for head and neck cancer - Iseli, Tim A; Kulbersh, Brian D; Iseli, Claire E; Carroll, William R; Rosenthal, Eben L; Magnuson, J Scott (Otolaryngology-head and neck surgery, 2009)
To evaluate functional outcomes following transoral robotic surgery for head and neck cancer. Case series with planned data collection. Academic hospital. Between March 2007 and December 2008, 54 of 62 candidate patients underwent transoral robotic tumor resection. Outcomes include airway management, swallowing (MD Anderson Dysphagia Inventory), and enterogastric feeding. Tumors were most commonly oropharynx (61%) or larynx (22%) and T1 (35%) or T2 (44%). Many received radiotherapy (22% preoperatively, 41% postoperatively) and chemotherapy (31%). Endotracheal intubation was retained (22%) for up to 48 hours, tracheostomy less frequently (9%), and all were decannulated by 14 days. Most commenced oral intake prior to discharge (69%) or within two weeks (83%). A worse postoperative Dysphagia Inventory score was associated with retained feeding tube (P=0.020), age>60 (P=0.017), higher T stage (P=0.009), laryngeal site (P=0.017), and complications (P=0.035). At a mean 12 months' follow-up, 17 percent retained a feeding tube (9.5% among primary cases). Retained feeding tube was associated with preoperative tube requirement (P=0.017), higher T stage (P=0.043), oropharyngeal/laryngeal site (P=0.034), and recurrent/second primary tumor (P=0.008). Complications including airway edema (9%), aspiration (6%), bleeding (6%), and salivary fistula (2%) were managed without major sequelae. Transoral robotic surgery provides an emerging alternative for selected primary and salvage head and neck tumors with low morbidity and acceptable functional outcomes. Patients with advanced T stage, laryngeal or oropharyngeal site, and preoperative enterogastric feeding may be at increased risk of enterogastric feeding and poor swallowing outcomes.